A Novel Splice-Site Mutation in MSH2 Is Associated With the Development of Lynch Syndrome - Li, Juyi; Li, Yuanyuan; Ni, Haichun; Yang, Zhibin; Chen, Jian; Li, Yarong; Ding, Sheng; Jiang, Xiaowan; Wang, Mengjie; Li, Li; Lv, Xiaoyu; Ruan, Xiaoyun; et al. (Frontiers in Oncology, 2020)
Lynch syndrome (LS) is inherited in an autosomal dominant manner caused by germline mutations in mismatch repair (MMR) genes including MSH2, MSH6, PMS2 and MLH1 genes. This study aimed to analyze the molecular and clinical findings within the pedigree and propose an adequate individual prophylactic strategy for all mutation carriers. Here, A novel splicing mutation (c.1661+2 T>G) was identified in the MSH2 gene that was found to be co-segregated among affected family members with LS by using Whole exome sequencing (WES). The results of the RT-PCR confirmed that c.1661+2 T>G could cause 3 transcripts including 1 normal transcript and 2 aberrant transcripts. The 2 aberrant transcripts caused a premature termination codon TGA at the 6th nucleotide upstream of the MSH2 exon 11, giving the predicted product of the mutant MSH2 mRNA were truncated proteins of 505 amino acid residues (all exon 10 deletion) or 528 amino acid residues (82-nucleotides deletion in exon 10), resulting in the loss of region of interaction, ATP domain and post-translation modified residues of the MSH2. The results of the quantitative RT-PCR (qRT-PCR) showed that the level of the MSH2 mRNA was reduced to 1/4 in all patients as compared to controls. Our study reveals that the novel splicing mutation (c.1661+2 T>G) in the MSH2 gene causes LS and reaffirms the importance of genetic testing in LS. It provides a scientific foundation for accurate diagnosis and precise medical intervention for LS.